Metabolic Complications of Antipsychotic Therapy for Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs, 2010)
Seventy-three children with Tourette syndrome treated with antipsychotics were monitored for metabolic and neurologic side effects every six months in a study at University of Calgary, Alberta, Canada.